ETR 300 : Glorious Sdn. Bhd / Ezreen Mohd Razali ... [et al.] - Mohd Razali, Ezreen; Md Mokhtarudin, Anisah; Azman, Azlinda; Noraman, Nadziatul Shazwani; Abdul Wahab, Najwa (2002)
Glorious Sdn. Bhd was incorporated on the 23 June 2002 and registered with The Registrar of Business to undertakes Bathroom Specialist company. Situated at Bandar Perda, Bukit Mertajam in Penang. The location is strategic and we expected that this business is profitable since there are only few business based on bathrooms. Our business are selling a sort of thing regarding bathroom accessories and other big product. Such as basin, bidet, wc, and others. Although newly established, Gloriours Sdn. Bhd which is a 100% Bumiputra business, is a professionally managed establishment with emphasis on personalized and friendly service. With a strong foundation in a dedicated team with vast experience in many kinds of working range, it has the capabilities to provide excellent and reliable services to a growing list of clientele.